ANALISIS PENJADWALAN DISTRIBUSI PUPUK BERSUBSIDI MENGGUNAKAN METODE DISTRIBUTION REQUIREMENT PLANNING (DRP) (STUDI KASUS PADA PT. PETROKIMIA GRESIK) - Dewi Sukmawati; Bambang Irawanto (Jurnal Matematika, 2014)
ABSTRACT. The Distribution of products in PT. Petrokimia Gresik carried out on the demand of consumers of each district in the province. The distribution is run on irregular or random, either in time or quantity distribution. Activity affects the distribution of the total cost of inventory the company issued in the procurement of supplies, therefore the company needs to pay close attention to the application System of distribution’s activity to optimize the distribution of subsidized fertilizer schedule in order to maintain time and cost efficiency. Distribution Requirement Planning (DRP) is a method for handling the procurement of supplies in a multi-level distribution network. DRP method relates to the size of ordering lot and the amount of safety stock. DRP method reduce the total cost of inventory and the frequency distribution of activity by determining the distribution of effective scheduling in consideration that the distribution is done in accordance lot size or multiples thereof and the amount of safety stock required. From the research, the activity of distribution schedule of subsidized fertilizer is obtained in Region DC of Lampung in 2013 with the total stockpile cost 7.875.167.077 IDR of inventory at PT. Petrokimia Gresik within 9 months. Distribution of subsidized fertilizer each product that executed simultaneously on day 22 in each period to the 4 buffer warehouses in Lampung region. Keywords: